GIBBS FREE ENERGIES OF FORMATION OF RUO2, IRO2, AND OSO2: A HIGH-TEMPERATURE ELECTROCHEMICAL AND CALORIMETRIC STUDY - O'Neill H.St.C.; Nell J. (My University, 1997)
The Gibbs free energies of formation of RuO2, OsO2 and IrO2 have been determined by measuring the chemical potentials of oxygen (μO2) defined by the reactions M + O2 = MO2, where M = Ru, Os. or Ir, using an electrochemical method with calcia-stabilized zirconia (CSZ) solid electrolytes. Measurements were attempted in the temperature ranges from ∼870 K to 1620, 1270, and 1415 K for the Ru, Os, and Ir equilibria, respectively, but inspection of the results reveals that equilibrium could not be established below ∼930 K for all three reactions. For Ru + RuO2, the highest temperature data (above 1520 K) may be systematically affected by the onset of significant electronic conduction in the CSZ electrolyte, while the attempted measurements of the Os + OsO2 equilibrium above 1190 K are obscured by the disproportionation of OsO2 to gaseous Os oxides.